Grasping the Alternative: Reaching and Eyegaze Reveal Children’s Processing of Negation - Doyle, Alison W.; Friesen, Kelsey; Reimer, Sarah; Pexman, Penny M. (Frontiers in Psychology, 2019)
There is evidence that children begin to understand negation early in the preschool years, but children’s processing of negation is not well understood. We examined children’s processing of denial negation using a variant of the visual world paradigm called the Shopping Task. In this task, participants help a puppet to find the items on a shopping list, selecting from two potential items on each trial in response to the puppet’s affirmative (“the next item is an apple”) or negation (“the next item is not an orange”) sentence. In this binary decision context, participants’ eye gaze and reaching behavior were tracked as they selected the item the puppet wants. Participants were 78 4-5 year old children and a comparison group of 30 adults. Results showed that children took longer to process negation than affirmative sentences, and that this difference arose early in processing. Further, children’s eye gaze behavior suggested that on negation trials they regularly looked first to the negated object and were considering the negated meaning early in processing. Adults did not take longer to process negation than affirmative sentences, but their eye gaze behavior also indicated early consideration of negated meanings for negation sentences. We also examined relationships between children’s language and executive function skills and their processing of negation and found no significant relationships. We conclude that both adults and children activate to-be-negated information in the processing of negation. Children, however, are less efficient at processing negation in this context.